POTENTIAL FOR BIOGAS DEVELOPMENT FROM SEGIRI MARKET WASTE IN SAMARINDA CITY, EAST KALIMANTAN - Edhi Sarwono; Budi Nining Widarti; Aji Ery Burhandenny; Didit Suprihanto; Hairul Huda; Dhea Yolanda (Jurnal Chemurgy, 2022)
The Segiri Market waste has the potential to cause sources of disease, unpleasant odors, and interfere with aesthetics.  This study objectives are to estimate waste generation, potential volume and quality of biogas, as well as the potential for energy produced. The implementation of the procedure for sampling waste generation and composition in accordance with SNI 19-3964-1994 for 8 consecutive days.  The projected waste generation is based on the number of active traders and market capacity for five years. This study implements experimental method using 120 L volume using a ratio of 1:1 for chopped market garbage and cow rumen fluid.  The parameters are temperature, pH, biogas volume, and volatile solid values. The average volume and weight of waste generation in 2021 is 55.69 m3/day or 19,906.60 kg/day. The estimated biogas material harvested from the waste is 50.57 m3/day. This number is comprised of organic waste and inorganic waste with a total of 97.67% and 2.33% consecutively. The volume of biogas produced for 35 days is 156.45 mL, which equivalent to 1.05 kWh/day of electrical energy. The pH is in the range of 4.79 - 6.3, and the temperature is within 29.4oC - 31.9oC. Biogas can burn in the third to fifth weeks with a blue flame color. The estimated waste generation until 2025 reaches 61.31 m³/day which equivalent to 1.16 kWh /day of electrical energy. Keywords: Biogas, Market Waste, Tradisional Market, Waste Generation, Renewable Energy